2018
DOI: 10.1016/j.outlook.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Engaging national and regional partners to accelerate broad-scale implementation of nurse-developed interventions

Abstract: Only a small proportion of research-tested interventions translate into broad-scale implementation in real world practice, and when they do, it often takes many years. Partnering with national and regional organizations is one strategies that researchers may apply to speed the translation of interventions into real-world practice. Through these partnerships, researchers can promote and distribute interventions to the audiences they want their interventions to reach. In this paper, we describe five nurse scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…We have found that short worksheets can help mothers self-reflect and compare the helpfulness derived from supporters with the degree of distress anticipated in receiving help from that person. This exercise helps mothers choose helpers who may not be their typical supporters, but who provide more help and less conflict (Leeman et al, 2018). Mothers may not have social support they can immediately rely on, and thus may need to seek help through social services, volunteer organizations, faith communities, or the school system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that short worksheets can help mothers self-reflect and compare the helpfulness derived from supporters with the degree of distress anticipated in receiving help from that person. This exercise helps mothers choose helpers who may not be their typical supporters, but who provide more help and less conflict (Leeman et al, 2018). Mothers may not have social support they can immediately rely on, and thus may need to seek help through social services, volunteer organizations, faith communities, or the school system.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the individuals with severe depressive symptoms did not seek professional mental health care per the National Health and Nutrition Examination Survey data (Pratt & Brody, 2014). Therefore, screening of maternal depressive symptoms may be conducted through nontraditional settings such as Early Intervention services, pediatric clinic systems, or school systems (Beeber et al, 2017; Leeman et al, 2018; Shonkoff, Hauser-Cram, Krauss, Upshur, & Sameroff, 1992). Screening at nontraditional facilities for mothers requires coordination and appropriate training, which is best achieved by interdisciplinary team collaborations.…”
Section: Discussionmentioning
confidence: 99%
“…Offerings include training and career development programs, grants, conferences, and web‐based educational materials (Boehm et al, 2019). Many nurse scientists have participated in these offerings and are now serving as leaders within their local healthcare systems and universities and in key roles for implementation science organizations on a global scale that include implementation efforts, policy development, ethical considerations, and other areas of contribution (Boehm et al, 2019; Costa et al, 2017; Dolansky, Schexnayder, Patrician, & Sales, 2017; Leeman et al, 2018; Sales et al, 2016). Because of their knowledge and understanding of complex care environments, PhD and research doctorate nurses trained in implementation science can lead scientific efforts to identify effective strategies for implementation, determine facilitators and barriers, identify ethical and policy considerations, and evaluate impacts on client, service, and implementation outcomes across care delivery settings (Boehm et al, 2019).…”
Section: Phd Nurse Educational Preparation and Expertisementioning
confidence: 99%
“…These skills, in addition to nurses' implicit ability to problem solve and think critically, make them wellequipped to understand what implementation strategies are best for enhancing the incorporation of EBP into nursing and healthcare. There are nurse scientists already beginning to make a difference (Costa et al, 2017;Dolansky, Schexnayder, Patrician, & Sales, 2017;Leeman et al, 2018;Sales et al, 2016;Stetler, Ritchie, Rycroft-Malone, Schultz, & Charns, 2009), and more implementation-trained nurses are needed to continue this important work.…”
Section: Is Approachesmentioning
confidence: 99%